2020
DOI: 10.1111/1541-4337.12620
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid: A comprehensive review of the dietary sources, processing effects, bioavailability, beneficial properties, mechanisms of action, and future directions

Abstract: Chlorogenic acids (CGAs), a group of hydroxycinnamates, are generally abundant in everyday foods and beverages, most prominently in certain coffee drinks. Among them, the chlorogenic acid (CGA), also termed as 5-O-caffeoylquinic acid (5-CQA), is one of the most abundant, highly functional polyphenolic compounds in the human diet. The evidence of its health benefits obtained from clinical studies, as well as basic research, indicates an inverse correlation between 5-CQA consumption and a lower risk of metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
210
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(215 citation statements)
references
References 161 publications
(369 reference statements)
3
210
0
2
Order By: Relevance
“…Evidence is building up to address the broad application prospects of CGA in the fields of medicine, food, and husbandry (Chen et al, 2018;Naveed et al, 2018;Lu et al, 2020;Papuc et al, 2020). Our experiment found that dietary supplementation with CGA contributed to the growth and carcass performance of pigs (data not shown), fitting well with a previous report using a finishing-pig model (Xu et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Evidence is building up to address the broad application prospects of CGA in the fields of medicine, food, and husbandry (Chen et al, 2018;Naveed et al, 2018;Lu et al, 2020;Papuc et al, 2020). Our experiment found that dietary supplementation with CGA contributed to the growth and carcass performance of pigs (data not shown), fitting well with a previous report using a finishing-pig model (Xu et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Besides, clinical studies indicated that chlorogenic acid could decrease the risk of metabolic syndromes and chronic diseases (cardiovascular diseases, neurodegenerative diseases and liver diseases). Furthermore, chlorogenic acid also showed gastrointestinal protective and renoprotective effects [ 30 ]. Rutin might have potential for the treatment of ethanol-induced hepatotoxicity and exhibit a beneficial effect on regulating mitochondrial functions [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Potatoes can contain high amounts of CGA, with purple baby potatoes shown to have over 7 mg CGA g −1 DW, and tubers from primitive germplasm over 12 mg/g DW [ 160 , 213 ]. A modest 6-ounce portion of such potatoes would provide over 250 mg of CGA, which can surpass the amounts found in a cup of coffee, which is a much better-known source of CGA [ 214 ]. Curiously, red and purple potatoes typically have much greater amounts of colorless CGA than white potatoes.…”
Section: Phenolic Antioxidantsmentioning
confidence: 99%
“…CGA is readily bioavailable in humans [ 216 , 217 ], and is thought to have a remarkable number of health-promoting properties, including reduced risk of cancer, heart disease, strokes, Alzheimer’s and Parkinson’s [ 214 , 218 , 219 ]. CGA is also thought to be anti-hypertensive [ 220 ], and interestingly, a small human-feeding study with purple potatoes showed a hypotensive effect [ 221 ].…”
Section: Phenolic Antioxidantsmentioning
confidence: 99%